GAMBARAN PENGETAHUAN MENGGUNAKAN METODE BOOKLET PADA PENATALAKSANAAN BANTUAN HIDUP DASAR SISWA SMKN 1 SUNGAI PINANG - Maria, Insana; Fitriani, Fitriani; Hasaini, Asni; Chrisnawati, Chrisnawati (STIKES Suaka Insan, 2024)
Basic Life Support (BHD) is an emergency measure to clear the airway, assist breathing, and maintain blood circulation without using assistive devices. Knowledge and ability are needed through a form of BHD training for lay people so that professional and skilled human resources can be obtained when carrying out first aid measures for victims of illness or accidents through providing basic life support properly and correctly. This research aims to determine the description of knowledge using the booklet method in the management of Basic Life Support for Students at SMKN 1 Sungai Pinang. This research method is descriptive, this research design will use media in the form of booklets in the counseling process regarding Basic Living Assistance to Students of SMKN 1 Sungai Pinang. The sample in this research was 145 students at SMKN 1 Sungai Piang. The results of the research show that the level of knowledge of SMKN 1 Sungai Pinang students using the Booklet Method in the management of Basic Life Support is 39% in the enough Criteria. Conclusion: BHD training for lay people using the booklet method provides significant meaning in increasing knowledge. So that BHD training education will be effective using the booklet method.